A multicentre, randomised trial examining the effect of test procedures measuring emergence from post-traumatic amnesia. Issue 7 (30th March 2006) - Tate, R L; Pfaff, A; Baguley, I J; Marosszeky, J E; Gurka, J A; Hodgkinson, A E; King, C; Lane-Brown, A T; Hanna, J
Abstract : Background: Post-traumatic amnesia (PTA) tests that record different PTA durations in the same patient, thereby raising measurement accuracy issues, have been reported previously. A major problem lies in determining the end point of PTA. Aims: To delineate areas of discrepancy in PTA tests and to provide independent verification for a criterion signalling emergence from PTA. Methods: In a randomised design, two related PTA procedures were compared, one purportedly more difficult (Westmead PTA Scale, WPTAS) than the other (Modified Oxford PTA Scale, MOPTAS). Eighty two patients in the early stages of PTA were examined daily until emergence, by using the Galveston Orientation and Amnesia Test (GOAT) and the WPTAS/MOPTAS. A short battery of cognitive and behavioural measurements was made on three occasions: at the early stage of PTA (time 1), towards the end of PTA when the maximum score (12/12) was first obtained (time 2) and at the traditional criterion for emergence (scoring 12/12 for 3 consecutive days; time 3). Results: No significant difference was recorded in PTA duration between the MOPTAS and WPTAS. Both scales recorded longer PTA durations than the GOAT. By using Kaplan–Meier survival analyses, the WPTAS was found to show a more protracted pattern of emergence at the end stage of PTA than the MOPTAS. A time lag of ⩾1 week in the resolution of disorientation as compared with amnesia was observed in 59% cases. Significant improvements occurred on all independent measurements between time 1 and time 2, but on only 2 of 5 cognitive measurements between time 2 and time 3. Conclusions: Although no significant differences in the duration of PTA on the MOPTAS/WPTAS were recorded, emergence from the late stages of PTA occurred more promptly with the MOPTAS. The need for inclusion of both orientation and memory items in PTA tests is highlighted by the frequency of disorientation–amnesia dissociations. The patterns of results on the independent measures suggest that patients who are in PTA for > 4 weeks have probably emerged from PTA when they first score 12/12 on the MOPTAS/WPTAS, and this criterion can replace the traditional criterion.